ANALISIS PEMAHAMAN KONSEP SISWA DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINEAR TIGA VARIABEL (SPLTV) DI SMA NEGERI 9 PALU: Analysis Of Student’s Concept Understanding In Solving Problem Of Three Variabel Linear Equation System (SPLTV) Of The 10th Grade Of SMA Negeri 9 Palu - Larasati, Puja Ayu; Karniman, Tegoeh S.; Rizal, Muh. (Universitas Tadulako, 2023)
This study aims to obtain a description of the analysis of conceptual understanding in solving SPLTV problems for students with high, medium, and low mathematical abilities in class X SMA Negeri 9 Palu. In this qualitative research, to obtain data regarding students' conceptual understanding in solving SPLTV problems, test instruments and in-depth interviews were used. The results of the study show that: (1) Subjects have high mathematical abilities and are in good control of understanding concepts because they can restate the concepts contained in SPLTV, based on their existing knowledge so they can solve SPLTV problems, but for subjects with low abilities they have not fully understood restating the concept contained in SPLTV so that it has not been able to solve the problem; (2) Subjects have high mathematical abilities and are in good control of conceptual understanding because they can present the concept of algebraic forms into their mathematical models/algebraic equations, based on the knowledge they already have. However, low-ability subjects have not been able to do so; (3) subjects who have high abilities and are in control of indicators use, utilize, and choose certain procedures and operations that are good because they can use the right SPLTV solving method in accordance with the procedure and can take advantage of algebraic operations, but subjects with low abilities have not been able to do it ( 4) Subjects with high and moderate abilities can apply the concepts contained in SPLTV to solve problems based on the knowledge they already have, but subjects with low abilities have not been able to apply the concepts contained in SPLTV to solve problems.